2018
DOI: 10.1016/j.ajhg.2018.07.010
|View full text |Cite|
|
Sign up to set email alerts
|

Biallelic Mutations in ADPRHL2, Encoding ADP-Ribosylhydrolase 3, Lead to a Degenerative Pediatric Stress-Induced Epileptic Ataxia Syndrome

Abstract: ADP-ribosylation, the addition of poly-ADP ribose (PAR) onto proteins, is a response signal to cellular challenges, such as excitotoxicity or oxidative stress. This process is catalyzed by a group of enzymes referred to as poly(ADP-ribose) polymerases (PARPs). Because the accumulation of proteins with this modification results in cell death, its negative regulation restores cellular homeostasis: a process mediated by poly-ADP ribose glycohydrolases (PARGs) and ADP-ribosylhydrolase proteins (ARHs). Using linkag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
102
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(110 citation statements)
references
References 25 publications
3
102
0
Order By: Relevance
“…The increased sensitivity of human and mouse ARH3-deficient cells to hydrogen peroxide-induced cell death supports this theory (Tanuma et al 2016;. Loss-of-function mutations in ARH3 were linked to the pathogenesis of a rare recessive autosomal neurodegenerative disorder (Danhauser et al 2018;Ghosh et al 2018), suggesting that ARH3 contributes to the protection of neurons from endogenous ROS. In contrast, the mitochondrial function of ARH3 remains elusive, but current observations support two possibilities: First, ARH3 can degrade ADP-ribosylation artificially targeted to the mitochondrial matrix, and hence may be responsible for potential endogenous ADP-ribosylation in this compartment (Niere et al 2012).…”
Section: Arh3mentioning
confidence: 78%
“…The increased sensitivity of human and mouse ARH3-deficient cells to hydrogen peroxide-induced cell death supports this theory (Tanuma et al 2016;. Loss-of-function mutations in ARH3 were linked to the pathogenesis of a rare recessive autosomal neurodegenerative disorder (Danhauser et al 2018;Ghosh et al 2018), suggesting that ARH3 contributes to the protection of neurons from endogenous ROS. In contrast, the mitochondrial function of ARH3 remains elusive, but current observations support two possibilities: First, ARH3 can degrade ADP-ribosylation artificially targeted to the mitochondrial matrix, and hence may be responsible for potential endogenous ADP-ribosylation in this compartment (Niere et al 2012).…”
Section: Arh3mentioning
confidence: 78%
“…ARH3 is expressed in humans and mice, but not in Drosophila. Due to the partial overlap of PARG and ARH3 in PAR degradation activity, expression of ARH3 in PARG -/-Drosophila, rescued the reduced locomotion and life span (27). In contrast, ARH3 has a nonredundant activity with PARG in human and mouse cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, whole-exome or genome sequencing analysis of several families with affected individuals displaying age-dependent, recessive epilepsy-ataxia syndrome, showed that an ARH3 allele carrying various mutations was the top candidate of potentially deleterious genes (27). These mutations, which were located in 5 of the 6 exons of the ARH3 gene, included homozygous mutations introducing a premature stop codon, missense mutations leading to amino acid change, and homozygous deletions resulting in frameshift (27). In this article, we report a new family with ARH3 deficiency, a neurological clinical phenotype, and histological evidence of significant degeneration in the hippocampus, cerebellum, and cortical regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, ADPr is a reversible modification. Dysregulation of ADPr signalling as well as the unbalance between transferases' and hydrolases' activities has proven to have a role in many inherited and acquired human diseases, as in several neurological disorders and in cancer [36,39,70,[91][92][93][94][95].…”
mentioning
confidence: 99%